2002
DOI: 10.1128/mcb.22.2.644-656.2002
|View full text |Cite
|
Sign up to set email alerts
|

Germ Line Transmission of the Cdk4R24C Mutation Facilitates Tumorigenesis and Escape from Cellular Senescence

Abstract: Mutations in CDK4 and its key kinase inhibitor p16INK4a have been implicated in the genesis and progression of familial human melanoma. The importance of the CDK4 locus in human cancer first became evident following the identification of a germ line CDK4-Arg24Cys (R24C) mutation, which abolishes the ability of CDK4 to bind to p16INK4a . To determine the role of the Cdk4 R24C germ line mutation in the genesis of other cancer types, we introduced the R24C mutation in the Cdk4 locus of mice by using Cre-loxP-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 51 publications
7
156
1
1
Order By: Relevance
“…B, Splenocytes were isolated from two mice homozygous for a gene-targeted mutation of the gene cdk4. A point mutated version of cdk4 (R24C) that renders the protein incapable of binding the cki p15 Ink4b was targeted to the cdk4 locus in this previously described "knock-in" (17). WT splenocytes pooled from two mice were used as a control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B, Splenocytes were isolated from two mice homozygous for a gene-targeted mutation of the gene cdk4. A point mutated version of cdk4 (R24C) that renders the protein incapable of binding the cki p15 Ink4b was targeted to the cdk4 locus in this previously described "knock-in" (17). WT splenocytes pooled from two mice were used as a control.…”
Section: Discussionmentioning
confidence: 99%
“…Mice deficient for the cki p15 Ink4b were a generous gift from Dr. L. Wolff (Laboratory of Cellular Oncology, National Cancer Institute, Bethesda, MD), and have been described elsewhere (16). Mice harboring a gene-targeted mutation in the gene cdk4 (C24R) were a generous gift from Dr. S. Rane (Laboratory of Cell Regulation and Carcinogenesis, National Cancer Institute), and have been described in a previous publication (17).…”
Section: Micementioning
confidence: 99%
“…Cyclin-dependent kinase 4 (CDK4) is the chief catalytic subunit of the regulatory cyclin D that governs G1-to-S phase cell cycle progression (50). Dominant activating mutations affecting codon 24 of the CDK4 gene (R24H or R24C) render CDK4 insensitive to p16INK4 inhibition and are responsible for multiple neoplasia developing (50,51).…”
Section: Pik3ca Braf Egfr Kit Kras Hras Nras Pdgfra and Metmentioning
confidence: 99%
“…In addition, an activating CDK4 mutation (CDK4 R24C) was identified in patients with familial melanoma (Wo¨lfel et al, 1995;Zuo, 1996). A mouse model bearing that mutation displayed pancreatic hyperplasia and resulted in a wide spectrum of tumor development (Rane et al, 1999;Rane et al, 2002). These mice also developed invasive melanoma upon 7,12-dimethylbenz [a]anthracene (DMBA)/12-O-tetradecanoylphorbol-13-acetate (TPA) treatment (Sotillo et al, 2001b) and showed increased incidence of papillomas (Rane et al, 2002).…”
Section: Introductionmentioning
confidence: 99%